Rural Microcredit: Evidences From Albania - Marku, Egerta (European Scientific Journal, ESJ, 2016)
The purpose of this paper is to analyse the issues and concerns of Albanian rural credit, which is a powerful tool for enhancing production and productivity and for poverty alleviation. Further it highlights some of the strategies adopted by the Albanian government to increase the rural credit facilities in the rural area of Albania. The various problems faced by the farmers in applying for loans are analysed in detail. Rural credits serve as a tool for providing a sustainable livelihood for people who lives in these areas. Several organisations and Microfinance Institutions,. are playing a major role in providing rural credit facilities to rural Albania. to make the rural credit facilities available to most of the needy. In spite of several efforts put up by various organisations to increase the rural credit facilities, several challenges will prevail in the years to come.These aspects of the financial sector remain undervalued in mainstream literature on rural credit. With Albania being a nation in which more than 40 percent of people live in rural areas and rural credit being a powerful, and the only, tool for rural people in providing a means of livelihood, its importance and potential should be known to each individual.